Properties of small molecular drug loading and diffusion in a fluorinated PEG hydrogel studied by ¹H molecular diffusion NMR and ¹⁹F spin diffusion NMR - Mathias, Errol V; Aponte, Julia; Kornfield, Julia A; Ba, Yong (Colloid and polymer science, 2010)
Rf-PEG (fluoroalkyl double-ended poly(ethylene glycol)) hydrogel is potentially useful as a drug delivery depot due to its advanced properties of sol-gel two-phase coexistence and low surface erosion. In this study, ¹H molecular diffusion nuclear magnetic resonance (NMR) and ¹⁹F spin diffusion NMR were used to probe the drug loading and diffusion properties of the Rf-PEG hydrogel for small anticancer drugs, 5-fluorouracil (FU) and its hydrophobic analog, 1,3-dimethyl-5-fluorouracil (DMFU). It was found that FU has a larger apparent diffusion coefficient than that of DMFU, and the diffusion of the latter was more hindered. The result of ¹⁹F spin diffusion NMR for the corresponding freeze-dried samples indicates that a larger portion of DMFU resided in the Rf core/IPDU intermediate-layer region (where IPDU refers to isophorone diurethane, as a linker to interconnect the Rf group and the PEG chain) than that of FU while the opposite is true in the PEG-water phase. To understand the experimental data, a diffusion model was proposed to include: (1) hindered diffusion of the drug molecules in the Rf core/IPDU-intermediate-layer region; (2) relatively free diffusion of the drug molecules in the PEG-water phase (or region); and (3) diffusive exchange of the probe molecules between the above two regions. This study also shows that molecular diffusion NMR combined with spin diffusion NMR is useful in studying the drug loading and diffusion properties in hydrogels for the purpose of drug delivery applications.